Repudium i jego skutki prawne w Nowelach Justyniana - Kursa, Sławomir P. (Czasopismo Prawno-Historyczne, 2018)
In his Novels, Justinian strongly limited the legal possibilities of unilaterally sending a spouse away, by which he signifi cantly restricted the principle of freedom in marital causes and consciously contributed to the consolidation of the Catholic Church’s doctrine of indissolubility of marriage. Nevertheless, even he did not completely ban repudium. The point of departure of Justinian’s reform in this respect was Nov. 22 – a collection of provisions on the dissolution of marriage, including those on repudium. Its causes were radically restricted only by Nov. 117, which covered both repudium propter iustam causam and repudium bona gratia. In successive novels, Justinian increased penalties for unlawfully sending a spouse away. Finally, in Nov. 127, he introduced uniform penalties for men and women for committing repudium sine causa.